2023
DOI: 10.1111/sms.14320
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of meeting all three 24‐h movement guidelines and its correlates among preschool‐aged children

Abstract: The aim of the present study was twofold: first, to determine the meeting all three 24‐h movement guidelines in Colombian preschool‐aged children, and second, to explore the associations between different socio‐ecological correlates and the meeting of these guidelines. This was a cross‐sectional study with data from the Encuesta Nacional de Situación Nutricional (ENSIN‐2015) in Colombia, 2015–2016. The sample comprised 3002 low‐income preschoolers (3–4 years old, 50.7% boys). Data on physical activity, screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Other motives that explain the PA differences among boys and girls can be related to individual (e.g., age, self-efficacy), social (e.g., family support), and environmental factors 32 . Some studies also explored the correlates of meeting the 24-hs Movement Guidelines and found that, for example, being younger, being from a family with higher educational and socioeconomic levels, and not having a TV in the bedroom were positively correlated factors [33][34][35][36] . It has also been shown that the country's development index is strongly related to compliance with the 24-h Movement Guidelines 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Other motives that explain the PA differences among boys and girls can be related to individual (e.g., age, self-efficacy), social (e.g., family support), and environmental factors 32 . Some studies also explored the correlates of meeting the 24-hs Movement Guidelines and found that, for example, being younger, being from a family with higher educational and socioeconomic levels, and not having a TV in the bedroom were positively correlated factors [33][34][35][36] . It has also been shown that the country's development index is strongly related to compliance with the 24-h Movement Guidelines 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study involving preschool-aged children indicated that perceived availability of televisions at home was negatively associated with meeting all three movement guidelines. 21 Yet, it remains unclear whether similar associations exist among adolescents. To address this gap, further research is necessary to elucidate the intricate relationships between physical environments and adherence to 24-h movement guidelines in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…However, there remains a notable gap in our understanding of how these physical environmental characteristics relate to adherence to 24‐h movement guidelines in adolescents. A recent cross‐sectional study involving preschool‐aged children indicated that perceived availability of televisions at home was negatively associated with meeting all three movement guidelines 21 . Yet, it remains unclear whether similar associations exist among adolescents.…”
Section: Introductionmentioning
confidence: 99%